GAMBARAN FUNGSI PARU PADA MAHASISWA DAN RELAWAN LABORATORIUM DENGAN DAN TANPA RIWAYAT COVID-19 DI FAKULTAS KEDOKTERAN UNIVERSITAS ANDALAS TAHUN 2021 - Dhiaulhaq, Zalva Indira; Afriwardi, Afriwardi; Ermayanti, Sabrina; Irawati, Lili; Russilawati, Russilawati; Putri, Biomechy Oktomalio (SINERGI : Jurnal Riset Ilmiah, 2025)
Over the past two years, the COVID-19 pandemic has infected many individuals worldwide. Indonesia is one of the countries affected. This virus primarily infects the respiratory system. Some survivors have reported experiencing persistent symptoms after recovering from COVID-19, with some experiencing such symptoms for months. These persistent symptoms can also be referred to as long COVID-19. The purpose of this study is to determine the pulmonary function profile in medical students and laboratory volunteers with and without a history of COVID- 19 at the Faculty of Medicine, Andalas University. This is an observational study with a cross-sectional approach using a total sampling technique. The sample size is 43 COVID-19 survivors and 53 without history of COVID-19 from medical students and laboratory volunteers at the Faculty of Medicine, Andalas University. It is concluded and recommended that the respondents in this study have an average pulmonary function (FEV1, FVC, and FEV1/FVC ratio) in the normal category, with males being the majority among COVID-19 survivors and females among non-COVID-19 survivors.